Isolation and study of a ubiquitously expressed tomato pectin methylesterase regulatory region - Tiznado-Hernández, Martín-Ernesto; Gaffe, Joel; Handa, Avtar K. (Electronic Journal of Biotechnology, 2004)
Pectin methylesterase (PME) is an enzyme located in the plant cell wall of higher plants whose physiological role is largely unknown. We had isolated a PME gene from a tomato genomic library, including 2.59 kb of 5´ flanking region and the coding region. Both coding and promoter region were sequenced and computer analyzed. Tobacco transgenic plants were created harboring constructs in which 2.596 Kb, 1.306 Kb and 0.267 Kb sizes of the promoter were driving the expression of β-Glucuronidase gene (GUS). GUS activity was studied by histochemical and fluorometric assays. Two introns of 106 and 1039 bp were found in the coding region and phylogenetic analysis placed this PME gene closer to genes from Citrus sinensis and Arabidopsis thaliana than tomato fruit-specific PME genes. In the promoter, it was found direct repeats, perfect inverted repeats and light responsive elements. GUS histochemical analysis showed activity in all plant tissues with the exception of pollen. The reduction in the promoter size induced a reduction in GUS activity in root, stem and leaf. Furthermore, root and leaf showed the highest and lowest activity, respectively. We had isolated a tomato PME gene with novel characteristics as compared with other known PME genes from tomato.